РЕЗУЛЬТАТЫ АПРОБАЦИИ КОРМОВ ДЛЯ ОСЕТРОВЫХ РЫБ ОТЕЧЕСТВЕННОГО ПРОИЗВОДСТВА В БАССЕЙНОВЫХ УСЛОВИЯХ КАПШАГАЙСКОГО НВХ (Experimental biology, 2015)
In this article given a price of effectively of the home preparing productive foods for sturgeon fishes in comparison with foreign foods, which were trialing in conditions of Capchagay SGF. Performed the dynamic of rate ofgrowth and lively the sturgeon fishes’ fingerlings in spite of feeding with these foods. Shown the shortcomings of quality of foreign foods and advantages of home foods in spite of breeding the wild forms of sturgeon fishes, and any advantages of foreign foods in comparison with home foods in spite of breeding the domestically forms, these advantages were turned out in process of breeding the fingerlings of fishes according to abasin technology.
Keywords: Capchagay fishes